Pedagogical Significance of Natural Language Programming in Introductory Programming - Muhammad Shumail Naveed; Muhammad Sarim (Journal of Basic & Applied Sciences, 2018)
Learning programming is hard for novice students. Complicated syntax and semantic of programming languages and lack of previous knowledge are the contributing factors behind the hardness of programming. Natural programming language allows to program in a natural language and thereby ease the programming. In this paper, it is ascertained whether natural programming language is fruitful in learning the elementary programming concepts and supportive in preparing students for introductory programming courses. The discussion included in this paper can be used to design supportive programming languages and formulating effective courses and learning material to ameliorate performance of students’ in learning of introductory programming environments.